(untitled) (Altre Modernità, 2011)
The success of the Revolution in Cuba modifies the place socially occupied by the black population, the cultural policies and the genre paradigms as well as their organizational ways. How this process affects writing? Our essay try to show the importance of the presence of afro-cuban in the written poetry during the revolutionary period in Cuba. Specifically, we are interested in highlighting the genres and ethnicity cross and his differentiation with respect, on the one hand, to what had been considered until the moment like black poetry, and on the other hand, to the institutional poetry, that coincident with the aesthetic paradigm established by the regime. The study around as it is located the subject woman-black in the Cuban cultural field is too broad to be face in this work. However, we try to study the Georgina Herrera’s case to show some of the textual strategies that she used for to be inserted in a tradition and a social literary circuit like the Cuban.